2021
DOI: 10.11646/zootaxa.5040.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Spirobranchus bakau sp. nov. from Singapore: yet another species of S. kraussii-complex (Polychaeta: Serpulidae)

Abstract: The intertidal serpulid polychaete Spirobranchus kraussii was originally described from South Africa and has since been reported in numerous sub (tropical) localities around the world. Recently, however, S. kraussii was uncovered as a complex of morphologically similar and geographically restricted species, raising the need to revise S. cf. kraussii populations. We formally describe S. cf. kraussii from Singapore mangroves as Spirobranchus bakau sp. nov. based on morphological and molecular data. Despite their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…bakau and A. amphitrite were found to thrive at salinity ranges encompassing 27 PSU , and were hence maintained at 27 PSU in this study. They were collected from mangroves along the northwest coast of Singapore, often with brackish water due to rainwater runoff and riverine inputs, predominantly from two major rivers in Johor (Sungei Pulai and Sungei Johor) …”
Section: Methodsmentioning
confidence: 58%
See 3 more Smart Citations
“…bakau and A. amphitrite were found to thrive at salinity ranges encompassing 27 PSU , and were hence maintained at 27 PSU in this study. They were collected from mangroves along the northwest coast of Singapore, often with brackish water due to rainwater runoff and riverine inputs, predominantly from two major rivers in Johor (Sungei Pulai and Sungei Johor) …”
Section: Methodsmentioning
confidence: 58%
“…A seawater salinity of 27 PSU was selected to balance both the survival needs of the model organisms used in the study and yet not cause extensive aggregation of the PMMA nanoparticles that they form large flocs that settle out of the water column. Both S. bakau and A. amphitrite were found to thrive at salinity ranges encompassing 27 PSU 25,42 and were hence maintained at 27 PSU in this study. They were collected from mangroves along the northwest coast of Singapore, often with brackish water due to rainwater runoff and riverine inputs, predominantly from two major rivers in Johor (Sungei Pulai and Sungei Johor).…”
Section: ■ Methods and Materialsmentioning
confidence: 67%
See 2 more Smart Citations
“…However, such wide, nearly cosmopolitan distributions were recently questioned (Hutchings and Kupriyanova 2018). Genetic studies revealed that this warm temperate intertidal species is restricted to South African coasts and that taxa under this name from other areas belong to a large complex of regionally distributed species (Simon et al 2019;Pazoki et al 2020;Sivananthan et al 2021).…”
Section: Introductionmentioning
confidence: 99%